Analisis Perhitungan Pajak Penghasilan Pasal 29 CV GI - April Dwi Anggraini; Diarany Sucahyati (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2024)
Research on CV GI, a company engaged in the gas industry, reveals the impact of fiscal corrections on Income Tax Payable (PPh). The purpose of this study is to determine whether the fiscal corrections made by the company are in accordance with the Financial Accounting Standards (SAK) and tax regulations and the amount of underpayment of Income Tax Payable. By using the descriptive analysis method, researchers describe and analyze data related to the calculation of Income Tax Article 29 at CV. GI. The results showed that there were differences between the fiscal corrections made by CV GI with the provisions of SAK and tax regulations. This difference results in changes in fiscal profit and taxable income (PKP). Based on the research findings, the company needs to improve its understanding of SAK and tax regulations related to fiscal correction, the company needs to review its fiscal correction policy to ensure compliance with SAK and tax regulations, and the company can consider assisting the fiscal correction process with professionals, such as tax consultants, to ensure accuracy and compliance with regulations. This research makes an important contribution in understanding the impact of fiscal correction on income tax. By implementing the recommendations provided, companies can minimize the risk of tax underpayment and ensure compliance with tax regulations.